Digital readiness of SMEs: An Insight from Indonesia - Kurnia Khafidhatur Rafiah; Sunu Widianto; Irsyad Kamal; Amaliya Shofiana; A. Malik Fajar; Agung Anggara Rudini (AFEBI Management and Business Review, 2022)
In the era of industrial revolution 4.0, digital technology is constantly improving in many areas of industry, particularly in business. It forces every business, whether large corporations or small businesses, to make various adjustments in order to keep up with the advancement of digital technology. They should be aware of how far their improvement and readiness have advanced in the digital era. This paper measures the digital readiness of SMEs and categorizes them into the level of digital readiness. The research examined the level of digital readiness among businesses, particularly small and medium-sized enterprises (SMEs) in West Java. A survey of 113 SMEs in West Java was conducted to assess their digital readiness. This research used a descriptive survey research approach. The research method itself is carried out by using a cross sectional survey method. Five variables used in this research include people, process, strategy, technology, and integration. Findings indicated that SMEs in Indonesia show a low level of readiness in relation to Industry 4.0. The majority of the respondents are aware about the phenomenon of digitalization, but they are currently not ready to adapt or use various innovations in their businesses. People, process, strategy, technology, and integration are the five variables analyzed, and the variable showing the best readiness to face digitization is people. SMEs business owners are still taking initial steps to identify the most appropriate strategy to approach industrial revolution 4.0. SMEs must take advantage of existing opportunities, especially with the availability of various information and data to develop business and make decisions. In general, the majority of businesses in Indonesia are small and medium-sized enterprises (SMEs) that are aware of the development of digitalization but are hesitant to implement it and require extensive assistance from various parties to understand and implement digitalization in their business.